Pacu embryos submitted to different cooling protocols - Streit Júnior, Danilo Pedro; Digmayer, Melanie; Ribeiro, Ricardo Pereira; Sirol, Rodolfo Nardez; Moraes, Gentil Vanini de; Galo, Juliana Minardi (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the percentage of hatching after cooling of pacu (Piaractus mesopotamicus) embryos at -8oC for six hours, treated with cryoprotectant solutions, to obtain a cooling protocol for the specie. There were 2.400 embryos in post-gastrula stage development, in seven cryoprotectants solutions and control with three replicates, in completely randomized design. Ethylene glycol and honey-jelly were inappropriate. The substitution of 50% sucrose did not produce positive results. The combination of methanol (9%) and sucrose (17.5%) performed 69.2% of hatching and is recommended for cooling of pacu embryos at -8 °C for six hours.